Adolescent Resilience Education Edukasi Resiliensi Remaja pada Model Pengembangan Kampung Ramah Keluarga (Studi Kasus Desa Ciherang, Kecamatan Dramaga, Kabupaten Bogor) - Euis Sunarti; Rahmi Damayanti; Syamila Karunia; Aliya Faizah Fithriyah (Institut Pertanian Bogor, 2025)
Adolescents, as national assets and agents of social transformation, face increasingly complex global challenges, particularly in the era of disruption and digitalization. Strengthening resilience is essential for preparing adolescents to navigate these changes effectively. In response to this need, the Dosen Pulang Kampung team from DPMA IPB University implemented an adolescent resilience education program based on the Kampung Ramah Keluarga development model. This program aimed to enhance adolescents' awareness and skills in building resilience. The program employed the Participatory Action Research (PAR) method, emphasizing active engagement in learning, reflection, and action. This approach empowers adolescents by providing opportunities to identify challenges, explore solutions, and implement strategies suited to their needs and environmental conditions. The educational procedure was conducted through lectures, questionnaire assessments, group discussions, and SWOT analysis exercises. The program was conducted over five sessions from April to June 2024, involving 27 participants. The findings revealed that the program significantly improved adolescents' understanding of the challenges posed by digital disruption while enhancing their knowledge of developmental tasks, leadership, and self-management skills. Discussions and SWOT analysis exercises further enabled participants to identify their strengths, weaknesses, opportunities, and threats within their environment, fostering their readiness to become resilient, well-rounded individuals capable of contributing to the development of a family friendly community.